‘Some hid in the sea’: Islamist attack on Mozambique town a turning point in Africa’s ignored war - Cotterill, Joseph (Financial Times, 2021)
French group Total suspends work at gas plant near Palma despite authorities’ claims order has been restored
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; security / segurança

Hunger spreading as Mozambique crisis reaches tipping point - Marima, Tendai (AlJezeera, 2021)
Thousands of people shelter in displacement camps with limited food supplies across Cabo Delgado following Palma attack.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; security / segurança

As Militants Seize Mozambique Gas Hub, a Dash for Safety Turns Deadly - Goldbaum, Christina; Schmitt, Eric; Walsh, Declan (The New York Times, 2021)
An agonizing choice for nearly 200 people holed up in a hotel as gunmen roamed unchecked: Wait overnight for rescue? Or make a run for it?
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; private sector / setor privado